Direct Carotid-Cavernous Fistula Caused by Internal Carotid Artery Perforation by a Microcatheter Body during Mechanical Thrombectomy - Miyamoto, Satoshi; Kato, Noriyuki; Yamazaki, Tomosato; Yamano, Akinari; Akutsu, Yoshimitsu; Yasuda, Susumu; Matsumaru, Yuji; Ishikawa, Eiichi (Asian Journal of Neurosurgery, 2022)
Rapid advances in emergent mechanical thrombectomy have resulted in a higher occurrence of arterial perforations during neurointerventions. Here, we report a case of internal carotid artery (ICA) perforation during mechanical thrombectomy in a 78-year-old man with a left middle cerebral artery occlusion. The ICA was perforated by a microcatheter during thrombectomy, forming a direct carotid-cavernous fistula. A two-stage drainer occlusion was conducted because of cortical venous reflex aggravation and ocular symptoms. Here, we report the perforation details and treatment, adding to evidence that ICA perforation with the microcatheter body is a concern during mechanical thrombectomy.
Keywords: direct carotid-cavernous fistula; mechanical thrombectomy; internal carotid artery perforation; perforation with the microcatheter